FLOW HYDROGRAPH GENERATION FOR MELAWI SUB-WATERSHED USING THE SNYDER SYNTHETIC UNIT HYDROGRAPH MODEL - Muslim, Alfin Islami Ibnu; Soeryamassoeka, S. B.; Nirmala, Azwa (Jurnal Teknik Sipil, 2024)
The study, titled "Flow Hydrograph Generation for Melawi Sub-Watershed Using the Snyder Synthetic Unit Hydrograph Model," investigates the hydrological response of the Melawi Sub-Watershed in West Kalimantan to rainfall events using the Snyder Synthetic Unit Hydrograph Model (SUHM). This model, instrumental in areas with limited hydrological data, is well-suited for the Melawi Sub-Watershed. The analysis uncovers a peak discharge (Qp) of 13.671 m ³/sec with a time to peak (Tp) of 88.905 hours, highlighting the region"™s susceptibility to prolonged rainfall. The model"™s parameters, such as Ct and Cp, are used to generate accurate flow hydrographs, which are essential for flood management. The results show varying design discharges for different return periods (Q2 to Q100), providing critical data for flood risk mitigation and infrastructure planning. This research underscores the SUHM's effectiveness in flood forecasting and sustainable development, aiding in resilient flood management strategies and informed infrastructure design in the Melawi Sub-Watershed. The findings of this study also pave the way for future research in hydrology and flood management.